3D printing integrated with controlled delivery for musculoskeletal tissue engineering. Issue 3 (July 2017) - Tarafder, Solaiman; Lee, Chang H
3D printing is an emerging tool to fabricate scaffolds for tissue engineering and regenerative medicine, benefited by customized design, tunable internal microstructure and a wide range of applicable materials. As a recent technical advancement, 3D-printed scaffolds have been incorporated with a controlled delivery of growth factors and/or other bioactive cues to facilitate tissue regeneration, in addition to providing a temporal structural substrate for cell and tissue ingrowth. This review covers a number of the existing approaches to incorporate a controlled delivery system in 3D-printed scaffolds from hydrogel adsorption and surface coating to chemical integration and embedding microspheres. In addition, we discuss the advantages and disadvantages of each delivery method integrated in 3D-printed scaffolds, outstanding challenges and future directions.